Staff and patient perceptions of a community urinary catheter service. Issue 2 (30th March 2020) - Oswald, Freya C.; Young, Ellen; Denison, Fiona C.; Allen, Rosalind J.; Perry, Meghan
Abstract: Urinary catheters are used extensively throughout healthcare for various reasons including management of urinary tract dysfunction. The purpose of this study was to simultaneously explore both catheter user experience and staff perception of catheter services within community urinary catheter care. A questionnaire was conducted to investigate the views of community nursing staff. During the same time period, patients were interviewed about (a) catheter‐care standards and adherence to guidelines, (b) patients' feelings towards their catheter and (c) potential improvements to catheter practices and design. Sixty‐nine staff were surveyed. Although 97% of staff indicated they used local guidelines, in up to 62% of cases findings suggested practices in sending urine samples for culture did not comply with guidelines. Then, 75% of staff were satisfied with catheter care, but weaknesses were identified in handover processes, communication between staff and patients, and excessive documentation. Staff results were compared with the findings from interviews of 29 long‐term urinary catheter users, demonstrating a higher level of satisfaction with catheter care among patients (86%). Patients and staff agreed that generally the impacts of their catheter on personal hygiene, sense of independence, sense of dignity and of patient happiness, were neutral (neither positive nor negative). However, regarding improvements to catheter practices and catheter design, 73% of staff but only 45% of patients suggested improvements in service, while 76% of patients but only 49% of staff suggested improvement in design. The study reveals general satisfaction with community catheter care, but indicates areas of potential improvements regarding communication, documentation and catheter design. When compared to patient responses, staff overall had a less positive view of patients perception of their relationship with their catheter.